2016
DOI: 10.1155/2016/4284093
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of Open, Laparoscopic, and Robotic Gynecological Surgeries

Abstract: Objective. To investigate patient knowledge and attitudes toward surgical approaches in gynecology. Design. An anonymous Institutional Review Board (IRB) approved questionnaire survey. Patients/Setting. A total of 219 women seeking obstetrical and gynecological care in two offices affiliated with an academic medical center. Results. Thirty-four percent of the participants did not understand the difference between open and laparoscopic surgeries. 56% of the participants knew that laparoscopy is a better surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Such perceptions were associated with the robot being perceived as an artificial intelligence with automated functions to carry out invasive procedures, without the assistance of a surgeon. This supports work by Irani et al [14], where more than 65% of the participants were unaware that the surgeon directly controls the manoeuvre of one or more robotic arms through a computer-controlled system.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Such perceptions were associated with the robot being perceived as an artificial intelligence with automated functions to carry out invasive procedures, without the assistance of a surgeon. This supports work by Irani et al [14], where more than 65% of the participants were unaware that the surgeon directly controls the manoeuvre of one or more robotic arms through a computer-controlled system.…”
Section: Discussionsupporting
confidence: 86%
“…However, research has consistently demonstrated that patient understanding of robotic-assisted surgery is poor. Irani et al [14] examined patient knowledge and understanding of the differences between open, laparoscopic and robotic-assisted surgery and found that 34% 1 3 of participants did not understand the difference between open and laparoscopic surgeries and 46% of the participants did not understand the difference between laparoscopic and robotic procedures. Furthermore, 67.5% of participants were not aware that the surgeon directly controls the movement of one or more robotic arms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study found that the most important factors associated with patient decision-making regarding MIS are: Safety, degree of postoperative pain, and recovery time [12]. Furthermore, despite the widespread use of RAS in populations, such as in the USA, public acceptance of this technology still poses a challenge and has been found to be directly related to the public's educational level and experience with the use of social media [13]. Interestingly, individuals who like to use computer technology are more accepting of the use of advanced healthcare technology, including RAS [14].…”
Section: Introductionmentioning
confidence: 99%
“…3 Meanwhile, patients are unable to comprehend the difference between various surgical approaches to the same pathology with only approximately one-third of them understanding that the "robot" is, in fact, a teleoperator where the surgeon controls every move of the "robot's" arms to perform the surgery. 4 Physicians, themselves, often receive conflicting information on the practical and theoretical uses of this technology, especially in the setting of fertility preserving procedures. It is, therefore, a critical time to review robotic applications in reproductive surgery.…”
mentioning
confidence: 99%